Instruction in Co-Teaching in the Age of Endrew F. Issue 1 (January 2021) - Weiss, Margaret P.; Glaser, Holly
The recent Supreme Court decision in Endrew F. v. Douglas County School District focused attention on outcomes for students with disabilities. It is not just about participating; it is about the instruction and outcomes from those services. Co-teaching is a prevalent service delivery model for students with disabilities who access the general curriculum. Much has been written about co-teaching but not necessarily about the instruction that takes place in a co-taught classroom. In this case study, we present a preliminary investigation of a conceptual model for instruction in co-teaching. We report teacher and student behavior change as well as contextual variables that had an impact on implementation.